2022
DOI: 10.1016/j.brs.2021.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Toward focused ultrasound neuromodulation in deep brain stimulator implanted patients: Ex-vivo thermal, kinetic and targeting feasibility assessment

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…240 It becomes clear that TUS has excellent properties for targeting deep brain regions, perhaps even combinable and applicable in DBS patients and beyond. 157 Sarica et al (2022) recently published their work in an ex-vivo setting regarding appropriate parameters for TUS to enhance adaptability of such applications and to not produce hazardous temperatures on DBS lead. 157 Alternatively, non-invasive stimulation 65,241,242 but also invasive 63,65,242 stimulation of the cerebellum has been tried out for post-stroke recovery.…”
Section: Spinal Cord Stimulation (Scs)mentioning
confidence: 99%
See 2 more Smart Citations
“…240 It becomes clear that TUS has excellent properties for targeting deep brain regions, perhaps even combinable and applicable in DBS patients and beyond. 157 Sarica et al (2022) recently published their work in an ex-vivo setting regarding appropriate parameters for TUS to enhance adaptability of such applications and to not produce hazardous temperatures on DBS lead. 157 Alternatively, non-invasive stimulation 65,241,242 but also invasive 63,65,242 stimulation of the cerebellum has been tried out for post-stroke recovery.…”
Section: Spinal Cord Stimulation (Scs)mentioning
confidence: 99%
“…157 Sarica et al (2022) recently published their work in an ex-vivo setting regarding appropriate parameters for TUS to enhance adaptability of such applications and to not produce hazardous temperatures on DBS lead. 157 Alternatively, non-invasive stimulation 65,241,242 but also invasive 63,65,242 stimulation of the cerebellum has been tried out for post-stroke recovery. Preclinical studies proved DBS stimulation to the cerebellum for post-stroke conditions to be effective in rodents.…”
Section: Spinal Cord Stimulation (Scs)mentioning
confidence: 99%
See 1 more Smart Citation
“…TMS was recently used to verify target engagement and modulation of lateral cortex with LIFUS, and another study used DBS recordings in an ex-vivo model for confirmation. 33 , 44 More safety data are needed before recordings from implanted devices such as RNS or DBS in human subjects can be used to verify LIFUS’ effects. One can envision how this method may also be used for noninvasive mapping of the human brain given its ability to transcranially elicit neurophysiologic and/or clinical responses from innumerable brain regions.…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
“…Nowadays, low-intensity focused ultrasound (LIFUS) becomes widely used as a non-thermal, non-invasive approach for generating neuromodulation toward vision restoration ( Baek et al, 2017 ; Fomenko et al, 2018 ; Jiang et al, 2018 , 2019 ; Yuan et al, 2019 ). It has been repeatedly demonstrated that FUS can effectively stimulate the neurons in vitro ( Menz et al, 2017 ; Cafarelli et al, 2021 ), ex vivo ( Blackmore et al, 2019 ; Menz et al, 2019 ; Sarica et al, 2022 ), and in vivo ( Naor et al, 2012 ; Lee et al, 2015 ). For the vision restoration purpose, an acoustic retinal prosthesis (ARP) had been proposed for the first time by demonstrating a FUS neurostimulation of the retinal cells in anesthetized wild-type rats ( Naor et al, 2012 ).…”
Section: Ultrasound Stimulation Of Retina and Visual Cortexmentioning
confidence: 99%